Ethernet Over Coaxial (EoC) Cable Telemetry Over High Voltage Dc And High Power Ac For Airborne Sonar Applications - G., Manoj; Ramesh, R.; Kundukulam, Sona O. (Defence Science Journal, 2023)
We have proposed a new passive component-based coupling scheme to simultaneously transmit high power AC, high voltage DC and high speed data through a long, single core coaxial cable, particularly for Airborne Sonar applications. This method is intended to replace the bulky multicore cables with single core coaxial cables that are compact and effective for transmitting data over long distances. This coupling scheme consists of three couplers to superimpose high power AC, high voltage DC and high speed data at the onboard end of the cable, and three decouplers to separate them at the remote end. The long cable, couplers, decouplers and the acoustic transducer are represented by their corresponding equivalent circuits that are cascaded together to construct the complete network. Power loss in the circuit is minimised by providing impedance matching networks in the form of a T-network transmission line and a tuning coil. The Ethernet over Coaxial (EoC) module can transmit high speed Ethernet data at the rate of 10/100 Mbps for telemetry from onboard to remote units and vice versa. DC voltages up to 300 V are coupled to the single core coaxial cable from the onboard unit and superimposed with high power AC signals and high-speed data. Passive filter-based coupling and decoupling schemes are demonstrated. Network simulation studies and experimental studies are carried out to verify and validate the equivalent circuit model. The transfer functions of each set of couplers and decouplers are determined independently as well as collectively and their effects on the underwater acoustic performance of the system are studied. The model resuls are found to agree with experiments. The proposed system is capable of generating an acoustic Source Level of about 195 dB with the supply of 125 V continuous wave (CW) AC signals, with simultaneous transmission of data at 10 Mbps and DC supply of 260 V from the on-board unit to the remote unit at the end of a coaxial cable of 200 m length. Introduction of impedance matching network is found to increase the source level by about 12 dB.